Improving the Environmental Risk Assessment of Substances of Unknown or Variable Composition, Complex Reaction Products, or Biological Materials. (16th September 2020) - Salvito, Daniel; Fernandez, Marc; Jenner, Karen; Lyon, Delina Y.; de Knecht, Joop; Mayer, Philipp; MacLeod, Matthew; Eisenreich, Karen; Leonards, Pim; Cesnaitis, Romanas; León‐Paumen, Miriam; Embry, Michelle; et al.
Abstract: Substances of unknown or variable composition, complex reaction products, or biological materials (UVCBs) pose unique risk assessment challenges to regulators and to product registrants. These substances can contain many constituents, sometimes partially unknown and/or variable, depending on fluctuations in their source material and/or manufacturing process. International regulatory agencies have highlighted the difficulties in characterizing UVCBs and assessing their toxicity and environmental fate. Several industrial sectors have attempted to address these issues by developing frameworks and characterization methods. Based on the output of a 2016 workshop, this critical review examines current practices for UVCB risk assessment and reveals a need for a multipronged and transparent approach integrating whole‐substance and constituent‐based information. In silico tools or empirical measurements can provide information on discrete and/or blocks of UVCB constituents with similar hazard properties. Read‐across and/or whole‐substance toxicity and fate testing using adapted emerging methods can provide whole‐substance information. Continued collaboration of stakeholders representing government, industry, and academia will facilitate the development of practical testing strategies and guidelines for addressing regulatory requirements for UVCBs. Environ Toxicol Chem 2020;39:2097–2108. © 2020 Health and Environmental Sciences Institute. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC.